Safer and Sustainable Co-precipitation Synthesis of NCA (LiNi0.80Co0.15Al0.05O2) Cathodes: Eliminating Ammonia in Favor of NaOH for pH Control - Shofirul Sholikhatun Nisa; Meidiana Arinawati; Cornelius Satria Yudha; Anisa Raditya Nurohmah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Developing safer and more sustainable synthesis routes for lithium ion battery cathodes is important for both environmental practice and laboratory education. This study reports an ammonia free oxalate coprecipitation route to synthesize LiNi0.80Co0.15Al0.05O2 (NCA), in which ammonia as the usual pH controller was fully replaced by sodium hydroxide (NaOH). NaOH dosage was varied at 20 g, 40 g, 60 g, and 80 g to control precipitation, precursor quality, and the properties of the final cathode after calcination and sintering. X ray diffraction confirmed formation of a layered α NaFeO2 type structure with R3m symmetry for all samples without detectable secondary phases. The 40 g NaOH condition showed the best structural ordering, reflected by a relatively high I(003)/I(104) intensity ratio associated with reduced cation mixing. Fourier transform infrared spectra verified oxalate ligand decomposition during thermal treatment and the appearance of metal oxygen lattice vibrations consistent with NCA formation. Scanning electron microscopy revealed that the 40 g NaOH sample produced more uniform particles with a narrower size distribution than other variants. Based on these results, the 40 g NaOH sample was selected for electrochemical evaluation and delivered an initial discharge capacity of about 110 mAh/g at 0.1 C in a full cell configuration. Overall, NaOH is demonstrated as an effective and safer substitute for ammonia in oxalate coprecipitation, enabling greener NCA synthesis protocols for research and teaching.